Challenges and Opportunities of Islamic Crowdfunding as a new Innovative mechanism to finance Startups - Djaber, Sotehi; Lotfi, Zeghbid Nassim (The journal of contemporary issues in business and government, 2023)
This study aims to explore the applicability of Islamic crowdfunding as an alternative fund to finance Startups Islamic crowdfunding platforms are based on cooperation (Taawun) and are designed to comply with the Shariah principles but is open to both Muslims and Non-Muslims. The funding should not have any element of interest (Riba), gambling (Maysir), non-permissible (Haram) and speculative (Gharar). These are some basic features, which distinguish from Conventional Crowdfunding platform and also the existence of Shariah supervisory board to ensure the transaction structures, processes and agreements are in compliance with Islamic law The study delves into the key components of Islamic crowdfunding, elucidating how it operates within the framework of Islamic finance. It scrutinizes various models of Islamic crowdfunding, including donation-based, reward-based, equity-based, and profit-sharing models, each catering to the diverse needs of entrepreneurs and investors. Additionally, the research explores the implications of these models on the startup ecosystem, considering the potential benefits and challenges faced by both startups and investors. In conclusion, this abstract underscores the potential of Islamic crowdfunding as a viable and ethical alternative for startup financing. And explores the burgeoning intersection of Islamic finance principles and contemporary startup financing through crowdfunding platforms. Traditional Islamic finance is rooted in Shariah law, which prohibits the charging or receiving of interest and promotes ethical and socially responsible investments. In contrast, startups often rely on conventional financing methods that may conflict with these principles. Islamic crowdfunding emerges as an innovative solution to bridge this gap, providing a Shariah-compliant avenue for entrepreneurs and investors alike.